1998
DOI: 10.1016/s0370-2693(98)00888-0
|View full text |Cite
|
Sign up to set email alerts
|

Grand unification of the sterile neutrino

Abstract: The simplest way to simultaneously understand all existing indications of neutrino oscillations from solar and atmospheric neutrino deficits and the LSND experiment, seems to be to postulate a sterile neutrino. We present a realistic grand unified model based on the gauge group SO(10) × SO(10) that leads to the desired masses and mixings for the sterile and the known neutrinos needed to understand the above observations while fitting those of the known charged fermions. The model is a grand unified realization… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 21 publications
0
50
0
Order By: Relevance
“…However, we have not referred to the neutrino masses. Concerning this problem, Brahmachari and Mohapatra have recently showed that one 10 and one 126 model is incompatible with large ν µ -ν τ mixing angle [7]. Since there are many possibilities for neutrino mass generation mechanism, we are optimistic about this problem, too.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…However, we have not referred to the neutrino masses. Concerning this problem, Brahmachari and Mohapatra have recently showed that one 10 and one 126 model is incompatible with large ν µ -ν τ mixing angle [7]. Since there are many possibilities for neutrino mass generation mechanism, we are optimistic about this problem, too.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Singlet neutrinos with masses relevant to oscillation experiments and dark matter can arise in grand unified models [26], string-inspired models [27], and models with large extra dimensions [28,29]. In reverence to Occam's razor, the minimalist model of Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Another [14] involves sterile neutrinos associated with a parallel hidden sector of nature, as suggested in some superstring and supergravity theories. Yet another associates the sterile neutrino with the light (10 −3 eV) Kaluza-Klein modes associated with a large (mm) extra dimension [15].…”
Section: Light Sterile Neutrinosmentioning
confidence: 99%
“…For light Majorana neutrinos, the amplitude is proportional to m νe , defined in (14). The current upper limit of 0.35 eV at 90% is from the Heidelberg-Moscow experiment.…”
Section: More Distant Possibilitiesmentioning
confidence: 99%